Effect of some Growth Hormones on Seed Germination and Seedling Growth of some Savanna Tree Legumes - Ebofin, A. O.; Agboola, D. A.; Aduradola, A. M.; Ayodele, M. S. (Indian Forester, 2004)
Studies were made on the effect of some growth hormones including Indole Acetic Acid (IAA) , Indole Butyric Acid (lBA) , Kinetin and Gibberellic Acid (GA3) on seed germination and seedling growth of four savanna tree legumes. The tree species include Prosopis africana (Guil & Perr) Taub (Mimosoidae); Parkia biglobosa (Jacq) R. Br. Ex G. Don (Mimosoidae); Albizia lebbek (Linn.) Benth (Mimosoidae) and Senna siamea (Lam) Irwin Barneby (Caesalpinoidae). 0.01-0.04ppm IAA enhanced germination in A. lebbek , P. biglobosa , P. africana and S. siamea. 0.01-0.05ppm IBA enhanced germination in P. africana and S. siamea. 0.01-0.05ppm kinetin retarded germination in P. biglobosa , P. africana and S. siamea. 0.01-0.05ppm. GA3 enhanced germination in A. lebbek and P. africana. 0.01-0.05 ppm IAA enhanced plant height and dry weight in the seedlings of the four tree species. 0.01-0.03 ppm IBA enhanced plant height and dry weight in S. siamea and only plant height only in P. biglobosa. IBA (0.03-0.04 ppm) enhanced leaf number in P. biglobosa and A. lebbek. Kinetin (0.01-0.05 ppm) enhanced leaf number in P. biglobosa. GA3. enhanced leaf number and plant height in P. biglobosa and plant height in A. lebbek.